x^2(x^2k-y^2k)+y^2k(x-y)(x+y)为什么能被x+y整除

发布于2013-03-18 14:15 最佳答案
请采纳。+AB^(k-1)+B^k]
∴能被x+y整除。。;+。,y²x^2(x^2k-y^2k)+y^2k(x-y)(x+y)
=x^(2k+2)-y^(2k+2)
=(x²)^(k+1)-(y²=A。

有疑问;)^(k+1)
设x²。+AB^(k-1)+B^k]
=(x+y)(x-y)[A^k+A^(k-1)B+A^(k-2)B²,(便于书写)
原式=(A-B)[A^k+A^(k-1)B+A^(k-2)B²+;若满意,谢谢。,请追问;=B
追问
原式=(A-B)[A^k+A^(k-1)B+A^(k-2)B²+。。。+AB^(k-1)+B^k]?用了什么方法?
追答
a^n-b^n=(a-b)[a^(n-1)+a^(n-2)b+a^(n-3)b²+。。。+ab^(n-2)+b^(n-1)]

其他回答

原式=kx^2(x^2-y^2)+ky^2(x-y)(x+y)
=kx^2*(x+y)(x-y)+ky^2(x-y)*(x+y)
=k(x+y)(x-y)[x^2+y^2]
所以,能被x+y整除.
追问
你的k是怎么跑出来的?
追答
k是提出来的公因式.
370116 | 发布于2013-03-18 13:38
评论

为您推荐: